2011
DOI: 10.1509/jmkg.75.3.132
|View full text |Cite
|
Sign up to set email alerts
|

It's Got the Look: The Effect of Friendly and Aggressive “Facial” Expressions on Product Liking and Sales

Abstract: When designing their products, companies try to employ shapes that are both emotionally appealing and compatible with the brand's image. One way to accomplish these aims is to anthropomorphize a product's appearance. The current research investigates how people decode emotional "facial" expressions from product shapes and how this affects liking of the design, using three studies in the domain of cars and one in the domain of cellular phones. In accordance with theories on the perception of human faces, the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
190
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(216 citation statements)
references
References 42 publications
5
190
1
8
Order By: Relevance
“…Prior research has investigated emotion and anthropomorphism [2], and found no direct impact on emotions when the anthropomorphic products carried a neutral or mild emotion [2]. However, when the anthropomorphic product exhibits strong positive emotion, it can trigger both high positive valance and high arousal [45].…”
Section: Research Hypothesesmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior research has investigated emotion and anthropomorphism [2], and found no direct impact on emotions when the anthropomorphic products carried a neutral or mild emotion [2]. However, when the anthropomorphic product exhibits strong positive emotion, it can trigger both high positive valance and high arousal [45].…”
Section: Research Hypothesesmentioning
confidence: 98%
“…We know anthropomorphism has an impact on attitude and behavior [35,68,48,45,15]. Researchers looked into how individuals perceive and react to a computer, and whether they treat computers as real humans.…”
Section: Overview Of Anthropomorphismmentioning
confidence: 99%
“…Marketing Research Association whitepaper [20] discusses the applications of facial recognition technology in the field of marketing research such as measuring consumer emotions and interest, for eye tracking in the areas of retail, consumer goods, websites etc. Jan R. Landwehr et al [21] have expressed how the study of facial expressions can be used for product design by analysing consumer expressions and analysing whether they like the design of a product and if it influences sales of that product. P.M.A.…”
Section: Background Literaturementioning
confidence: 99%
“…Una de las razones del éxito de estos iconos es que a los individuos les gusta atribuir característi-cas humanas a los objetos, proceso conocido como "antropomorfismo", y que genera una respuesta afectiva hacia los productos con independencia de sus atributos restantes (Delbaere, McQuarrie & Phillips, 2011;Landwehr, McGill & Herrmann, 2011). Por otra parte, las asociaciones que evoca el personaje de marca suelen trasladarse a la imagen que los individuos tienen del producto (Keller, 2008;De Iulio, 2010), impactan en las experiencias afectivas y sensoriales del consumidor (Delgado et al, 2013) e incluso generan sentimientos de comunidad en los miembros de una organización (Cayla, 2013).…”
Section: Objetivos Del Estudio Y Fundamentos Teóricosunclassified